Energy Management in Smart Grid with Various Load Patterns - Padmanabha Raju Chinda, B.Varshini, B.Harsha Naga Karthik, Ch.Venkata Rajesh Kumar, G.Manoja (International Journal of Advanced Science and Technology, 2020)
Power generation from sun powered force, wind power and other sustainable power sources is expanding, and their fluctuation acquaints new difficulties with the current power framework, which can't adapt adequately to exceptionally factor and distributed energy resources. The development of smart grid technologies in late year has seen a change in outlook in rethinking the electrical arrangement of things to come, in which controlled reaction of the demand side is utilized to adjust vacillations and irregularities from the generation side. Demand response and real-time pricing applications are part of the solution to mitigate the rising peak demand by allowing utilities to control consumer’s smart appliances and changing the behaviour of consumer’s electricity consumption. DG will reduce the need for larger centralized capacity investments and also increase efficiencies of power met at the end user by not having to be delivered over long congested transmission lines. The main aim of this paper is to design an optimal smart grid unit sizing, and perform optimal energy management. Various cases are made and contrasted with legitimize the chose innovations and their individual costs.Keywords: Smart grid, Energy Management System, DER, Fuel Cell, Battery Storage.